2006
DOI: 10.1128/iai.74.3.1692-1698.2006
|View full text |Cite
|
Sign up to set email alerts
|

Induction of a Novel Chicken Toll-Like Receptor following Salmonella enterica Serovar Typhimurium Infection

Abstract: Toll-like receptors (TLRs) are a group of highly conserved molecules that initiate the innate immune response to pathogens by recognizing structural motifs expressed by microbes. We have identified a novel TLR, TLR15, by bioinformatic analysis of the chicken genome, which is distinct from any known vertebrate TLR and thus appears to be avian specific. The gene for TLR15 was sequenced and is found on chromosome 3, and it has archetypal TIR and transmembrane domains and a distinctive arrangement of extracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
112
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(121 citation statements)
references
References 37 publications
7
112
1
1
Order By: Relevance
“…Cytokines, chemokines and nitric oxide are induced via chTLRs in response to their agonists (20,30,31). These findings imply that chTLR2 (30), chTLR15 (19), chTLR4 (20), chTLR5 (32), chTLR7 (33) and chTLR3 (34) are involved in leukocyte activation in chicken. Investigations pursuing chTLR-specific agonists/antagonists may give us a new strategy to design adjuvants and immune therapies for chicken infectious diseases in which BLP and PGN are involved as pathogenesis.…”
mentioning
confidence: 81%
“…Cytokines, chemokines and nitric oxide are induced via chTLRs in response to their agonists (20,30,31). These findings imply that chTLR2 (30), chTLR15 (19), chTLR4 (20), chTLR5 (32), chTLR7 (33) and chTLR3 (34) are involved in leukocyte activation in chicken. Investigations pursuing chTLR-specific agonists/antagonists may give us a new strategy to design adjuvants and immune therapies for chicken infectious diseases in which BLP and PGN are involved as pathogenesis.…”
mentioning
confidence: 81%
“…Under normal conditions, the mucus layer functions as a barrier between the content of the intestinal lumen and the epithelial cell layer, which is further protected from aberrant protease activity by secretory leukocyte peptidase inhibitor (35). In addition, previous studies have shown strong up-regulation of TLR15 in intestinal tissue after Salmonella infection and TLR stimulation (22,23), suggesting that, under healthy homeostatic conditions, the contact between TLR15 and normal intestinal proteases is limited. This form of regulation may represent an extra safeguard for the chicken for activation of the innate immune system by accidental exposure to proteases.…”
Section: Discussionmentioning
confidence: 99%
“…These experiments did not result in TLR15-mediated NF-κB activation, suggesting that the ligand for TLR15 differs from the known TLR activators. Previous reports indicated that TLR15 is expressed in the chicken cecum (22,23). In search for an activating ligand of TLR15 we therefore tested freshly isolated chicken cecal content.…”
Section: Tlr15 Is a Surface-localized Glycoprotein With A Typical Tlrmentioning
confidence: 99%
“…8 This constellation raises the question whether chicken cells are capable of responding to TLR agonists known to be active in mammals and whether cer tain ChTLRs might have unexpected ligand specificities. Our studies with freshly explanted spleen cells revealed that the chicken has no obvious deficits in recognition of pathogen-as- sociated molecular patterns.…”
Section: Discussionmentioning
confidence: 99%
“…3 7 Furthermore, a novel TLR gene, TLR 15, identified in chickens, is upregulated in response to heat-lkilled Salmonella enterica but shows no decisive similarity to the extracellular domain of any known mammalian TLR. 8 Interestingly, chickens appear to lack an ortholog of TLR9, 4 although chicken macrophages and peripheral blood mononuclear cells (PBMCs) can respond to CpG oligonucleotides. 9 In light of these differences and peculiarities of the chicken TLR system, it is important to know if the various chicken TLR orthologs have the same ligand specificities as their mammalian counterparts.…”
Section: Introductionmentioning
confidence: 99%